Tanner's target height formula underestimates final adult height in Korean adolescents and young adults: reassessment of target height based on the Korean National Health and Nutrition Examination Survey 2010-2019 - Sejin Kim; Jae Ho Yoo; Hee Won Chueh (BMJ Publishing Group, 2024)
Objective Estimating children's target height (TH) plays an important role in diagnosing, evaluating and treating many paediatric endocrinological diseases. However, in many countries, employing Tanner's formula to predict children's final adult height (FAH) is considered misleading. Therefore, this study aimed to re-evaluate the validity of Tanner's formula for predicting the TH of Korean adolescents and young adults and develop a new formula suitable for Korean children.Design/setting Data were derived from the Korean National Health and Nutrition Examination Survey 2010-2019.Patients A total of 2586 participants (1266 men, 1320 women) were included, excluding participants for whom Tanner's formula could not be calculated because of missing parental height data.Main outcome measures Tanner-based TH was compared with the FAH.Results The difference between Tanner-based TH and FAH was 4.86±0.178 cm for men and 4.81±0.150 cm for women. Sex-specific univariable and multivariable analyses were conducted to determine variables influencing positive height gap (greater than estimated TH). Both men and women with higher education levels were more likely to exhibit a positive height gap. Those with a history of chronic illness were less likely to exhibit a positive height gap, particularly in women. Using a new formula derived using linear regression analysis, the sum of parental heights explained 27.6% and 30.6% of the variance in sons' and daughters' heights, respectively.Conclusions Tanner's formula for calculating TH tended to underestimate FAH; hence, our new formula may offer a better alternative for estimating TH and evaluating growth in Korean children and adolescents.